The DEMATEL method explores the interdependent relationship structure and weights for diagnosis-related groups system - Zou, Tong; Jin, Yanjun; Chuang, Yen-Ching; Chien, Ching-Wen; Tung, Tao-Hsin (Frontiers in Public Health, 2022)
Purpose This study constructs a structure of interaction between dimensions and criteria within the diagnosis-related groups (DRGs) system from a quantitative system and identifies key factors affecting the overall performance of medical services. Method From September to December 2020, the influence relation structure diagram (IRSD) of the dimensions and corresponding criteria was developed from the practical experience of a group of domain experts, based on the DEMATEL method. Subsequently, all dimensions and criteria construct influential weights from a systems perspective. Finally, the main influential factors were identified based on the analysis results. Results The IRSD results showed that, in the overall performance of medical services, “Medical service capacity (C1)” was the main influential dimension, influencing both “Medical service efficiency (C2)” and “Medical service safety (C3).” At the criteria level, “Case-mix index (CMI) (C12),” “Time efficiency index (C21),” and “Inpatient mortality of medium-to-low group (C32)” were the main influential criteria in the corresponding dimensions. The influential weight results showed that “Medical service capacity (C1)” was also a key dimension. “Case-mix index (CMI) (C12),” “Cost efficiency index (C22),” and “Inpatient mortality of medium-to-low group (C32)” were the key criteria in their respective dimensions. Conclusion Patients and managers should first focus on the capacity of medical service providers when making a choice or deciding using the results of the DRGs system. Furthermore, they should pay more attention to medical safety even if it is not as weighted as medical efficiency.